TEACHER CANDIDATES' PERCEPTIONS OF SCHOOL ORGANIZATION: FUNDAMENTAL INCONSISTENCIES BETWEEN EXPECTATIONS AND EXPERIENCES - Cherubini, Lorenzo (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2009)
ABSTRACT. Preservice teacher-candidates enrolled in teacher education programs across Canada are exposed to the nuances of school organization during their practice-teaching assignments. Although the literature is full of scholarship about the concerns of new teachers, less attention has been given to school organizational factors as sources of dissonance for new teachers and preservice teacher education candidates. This study employed quantitative and qualitative methods to determine the effect of the practicum experience on prospective teachers’ beliefs about school organization in Ontario. The fundamental finding of the study was that participants’ experiences during their teaching-practicum assignments had a significantly negative effect upon their beliefs about school organization. PERCEPTIONS DES CANDIDATS À L’ENSEIGNEMENT FACEÀ L’ORGANISATION SCOLAIRE : INCOHÉRENCES FONDAMENTALES ENTRELES ATTENTES ET LES EXPÉRIENCES PRATIQUES RÉSUMÉ. Les candidats à l’enseignement inscrits au sein des programmes d’éducation des maîtres à travers le Canada sont exposés à la réalité de l’organisation scolaire au cours de leurs expériences pratiques d’enseignement. Or, si la littérature soulève abondamment les inquiétudes des nouveaux enseignants, peu d’attention a été accordée aux facteurs de l’organisation scolaire comme sources de dissonance pour les nouveaux enseignants et les candidats à la profession enseignante. En ce sens, cette étude utilise des méthodes quantitatives et qualitatives pour déterminer les effets des stages sur les croyances des aspirants enseignants relativement à l’organisation scolaire en Ontario. La conclusion fondamentale de cette étude est que les expériences des aspirants enseignants durant leurs travaux pratiques ont des effets significativement négatifs sur leurs croyances concernant l’organisation scolaire.